An Aridity Index‐Based Formulation of Streamflow Components. Issue 9 (4th September 2020) - Meira Neto, Antonio Alves; Roy, Tirthankar; de Oliveira, Paulo Tarso S.; Troch, Peter A.
Abstract: Direct runoff and baseflow are the two primary components of total streamflow, and their accurate estimation is indispensable for a variety of hydrologic applications. While direct runoff is the quick response stemming from surface and shallow subsurface flow paths and is often associated with floods, baseflow represents the groundwater contribution from stored sources (e.g., groundwater) to streams and is crucial for environmental flow regulations, and water supply, among others. L'vovich (1979) proposed a two‐step water balance partitioning, where precipitation is divided into direct runoff and catchment wetting, followed by the disaggregation of the latter into baseflow and evapotranspiration. Here, we investigate the role of the aridity index (ratio between mean‐annual potential evapotranspiration and precipitation) in controlling the long‐term (mean‐annual) fluxes of direct runoff and baseflow. We present an analytical solution beginning with similar assumptions as proposed by Budyko (1974), leading to two complementary expressions for the two fluxes. The aridity index explained 77% and 89% of variability in direct runoff and baseflow from 378 catchments within the continental United States, while our formulations were able to reproduce the patterns of water balance partitioning proposed by L'vovich (1979) at the mean‐annual timescale. Our approach can be used to further understand how climate and landscape controls the terrestrial water balance at mean‐annual timescales, while also representing a step toward the prediction of baseflow and direct runoff at ungauged basins. Key Points: Mean‐annual baseflow and direct runoff, estimated using a low‐pass filter, are controlled to first order by the aridity index The dependence of both fluxes on the aridity index is parameterized considering their limits when aridity index approaches 0 The proposed formulations can reproduce water balance partitioning of the L'vovich (1979) framework at the mean‐annual timescale